An exopolysaccharide from Leuconostoc mesenteroides showing interesting bioactivities versus foodborne microbial targets. (1st February 2023) - Bisson, Giulia; Comuzzi, Clara; Giordani, Elisa; Poletti, Denise; Boaro, Marta; Marino, Marilena
Abstract: An exopolysaccharide (EPS_B3) produced by a Leuconostoc mesenteroides strain isolated from a semi-hard Italian cheese was chemically and biologically characterized. HPLC-SEC, NMR, FT-IR and monosaccharide composition experiments were performed. Antimicrobial, antibiofilm, bifidogenic, antioxidant, and DNA-protective activity of EPS_B3 were also studied. Results revealed that EPS_B3 was a mixture of two high-molecular-weight dextran with low branching degree. Moreover, EPS_B3 displayed significant antibacterial activity against eight foodborne pathogens and inhibited biofilm formation by Listeria monocytogenes . EPS_B3 also evidenced bifidogenic activity, stimulating the growth of three probiotic bifidobacteria, and improving the tolerance of Bifidobacterium animalis subsp. lactis to oxygen stress. It also protected plasmid DNA from hydrogen peroxide damage. Only limited antioxidant capacity was observed. In conclusion, data suggest that EPS_B3 might be exploited in the context of functional foods especially for its marked antimicrobial activity as well as for the ability to improve the viability of bifidobacteria in probiotic foods. However, further studies should be carried out to assess the ability of EPS_B3 to reach intact the target site (i.e., gastrointestinal tract) to consider the possibility of use it as a new functional ingredient in foods. Graphical abstract: Unlabelled Image